Dynamics of Dualistic Motivation in Saving Behavior: A Qualitative Study on the Customer Experience of Bank BRI KCP Diponegoro Semarang - Ichsan Maulana; Abdur Rafik (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to gain a profound understanding of the motivations and experiences of depositors at PT. Bank Rakyat Indonesia (Persero) Tbk, Diponegoro Sub-Branch Office (KCP), Semarang. The research is driven by fluctuations in customer deposits that quantitative data alone cannot fully explain, necessitating a qualitative approach to explore the subjective meanings and considerations behind saving activities. Using a descriptive qualitative method, the study focuses on individual analysis. Data were collected via in-depth interviews with four purposively selected participants. While this sample size is small relative to the total population of KCP Diponegoro customers, it provides deep, contextual insights into the lived experiences of diverse customer segments that a broad statistical survey might overlook. Data analysis followed the Miles and Huberman model, including data reduction, display, and conclusion drawing. The results reveal a dualistic saving motivation: intrinsic factors (self-control, emergency funds, future orientation) and extrinsic factors (family influence, administrative requirements). BRI's primary appeal lies in accessibility, specifically ATM reach and the BRImo digital platform. Experience-wise, digital services offer efficiency, though face-to-face interactions are hampered by long queues and security concerns. Furthermore, customers expect products more adaptive to economic shifts. These findings provide practical implications for BRI KCP Diponegoro to improve offline service efficiency and strengthen system security. Theoretically, this research enriches the study of saving behavior within financial management through a more contextual, qualitative lens.